Gender-Based Association of Coronary Artery Calcification and Framingham Risk Score With Non-alcoholic Fatty Liver Disease and Abdominal Obesity in Taiwanese Adults, a Cross-Sectional Study - Tsou, Meng-Ting; Chen, Jau-Yuan (Frontiers in Cardiovascular Medicine, 2022)
Background: It is uncertain whether nonalcoholic fatty liver disease (NAFLD) or abdominal obesity (AO) has stronger associations with atherosclerosis and coronary artery disease (CAD) risk across different genders. This study was to determine the gender-based association of NAFLD and AO with subclinical atherosclerosis represented by coronary artery calcification (CAC) and CAD risk by Framingham risk score (FRS). Methods: A total of 1655 participants in a health-screening program (mean age: 49.44 years; males: 70.33%) were enrolled. Fatty liver and coronary artery calcium score (CACS) were measured via ultrasonography and multi-detector computed tomography (MDCT). The presence of CAC was defined as having a CACS > 0, intermediate to high CAD risk was defined as FRS ≥ 10%, while the presence of AO was defined as having a waist circumference (WC) of ≥ 90 cm for men and ≥ 80 cm for women. Subjects were divided into four groups according to the presence or absence of NAFLD and/or AO. Results: The proportion of subjects with CACS > 0 was highest in the AO-only group (overall: 42.6%; men: 48.4%; women: 35.8%); and FRS ≥ 10% was highest in the group with both abnormalities (overall: 50.3%%; men: 57.3%; women: 32.4%). After adjustment factors, the odds ratio (OR) for CAC and FRS was the highest in the group with both abnormalities (men: 1.61 [1.13–2.30] for CACS > 0 and 5.86 [3.37-10.20] for FRS ≥ 10%; women: 2.17 [1.13–4.16] for CACS > 0 and 6.31 [2.08-19.10] for FRS ≥ 10%). In men, the OR of NAFLD was higher than that of AO (1.37 [1.03–1.83] vs. 1.35 [1.02–1.79] for CACS > 0, 3.26 [2.13-4.98] vs. 2.97 [1.91-4.62] for FRS ≥ 10%). However, women with AO consistently showed increased OR for CACS > 0 (1.87 [1.11–3.16]) and FRS ≥ 10% (4.77 [2.01-11.34]). Conclusion: The degree of association of NAFLD and AO with CAC and FRS depends on the gender. NAFLD is more closely associated with CACS > 0 and FRS ≥ 10% in men and AO in women, respectively. NAFLD and AO could be considered independent determinants of CAC and FRS by gender.